Water societies and technologies from the past and present - Zhuang, Yijie; Altaweel, Mark (UCL Press, 2018)
Today our societies face great challenges with water, in terms of both quantity and quality, but many of these challenges have already existed in the past. Focusing on Asia, Water Societies and Technologies from the Past and Present seeks to highlight the issues that emerge or re-emerge across different societies and periods, and asks what they can tell us about water sustainability. Incorporating cutting-edge research and pioneering field surveys on past and present water management practices, the interdisciplinary contributors together identify how societies managed water resource challenges and utilised water in ways that allowed them to evolve, persist, or drastically alter their environment. The case studies, from different periods, ancient and modern, and from different regions, including Egypt, Sri Lanka, Cambodia, Southwest United States, the Indus Basin, the Yangtze River, the Mesopotamian floodplain, the early Islamic city of Sultan Kala in Turkmenistan, and ancient Korea, offer crucial empirical data to readers interested in comparing the dynamics of water management practices across time and space, and to those who wish to understand water-related issues through conceptual and quantitative models of water use. The case studies also challenge classical theories on water management and social evolution, examine and establish the deep historical roots and ecological foundations of water sustainability issues, and contribute new grounds for innovations in sustainable urban planning and ecological resilience.